MANAGEMENT OF BUMDES IN 2021 IN LUWO'O VILLAGE, POSIGADAN DISTRICT, BOLAANG MONGONDOW REGENCY SELATAN - Frista Iin Wahyuni; Nuzmerini Rauf; Ely Ibrahim (Journal of Hulonthalo Service Society (JHSS), 2022)
The objectives of this community service activity are: 1) to help BUMDes Luwo'o Posiga Subdistrict and develop a savings and loan unit based on an accounting information system with computer applications in making financial reports, 2) to improve the ability of BUMDes devices to operate accounting information systems with computer applications for making financial reporting. The method used is to provide training in the form of an introduction to the creation of a system in the savings and loan unit based on a technology-based accounting information system. Furthermore, the mentoring method is carried out on the implementation of a computer application-based accounting information system at the BUMDes Luwo'o savings and loan unit, Posigadan District, until the accounting information system can be run. The implementation of training and mentoring activities for the development of accounting information systems at BUMDes Luwo'o, Posigadan District has been running smoothly, both training activities and assistance in developing accounting information systems. The manager of BUMDes Luwo'o, Posigadan District, enthusiastically welcomed the implementation of community service activities, namely training and assistance in developing the accounting information system that had been designed.